Globalization and defence in the Asia-Pacific : Arms across Asia - Till, Geoffrey; Chew, Emrys; Ho, Joshua (London : Routlegde, 2009)
This edited volume examines the impact of globalisation on the economies, security policies and military-industrial complexes of the Asia-Pacific region.
Introduction/ Joshua Ho. Part 1: Theories of Globalization and Defence -- 2. Globalization and Armed Conflict Among Nations: Prospects Through the Lens of International Relations Theory/ Brian Pollins 3. Beyond Interdependence: Globalization, State Transformation and National Security/ Christopher W Hughes -- Part 2: Globalization and Defence Policy in the Asia-Pacific -- 4. Globalization and Military-Industrial Transformation in South Asia: An Historical Perspective/ Emrys Chew 5. The Impact of Globalization on Threat Perceptions and Defence Postures in Northeast Asia/ Guibourg Delamotte 6. The Impact of Globalization on Threat Perceptions and Defence Postures in Southeast Asia: Two views/ Rizal Sukma and K. S. Nathan 7. The Impact of Globalization on Threat Perceptions and Defence Postures in South Asia/ B. Rahman -- Part 3: Globalization and the Defence Economy in the Asia-Pacific -- 8. Defence and the Economy: An Introduction/ Ron Mathews 9. Globalization and Defence Industry in East Asia: Seeking Self-Sufficiency and Teaming Up for Dual-Use Technology/ Arthur S. Ding 10. Exploring Southeast Asia's Twenty-First Century Defence Economies: Opportunites and Challenges in the Era of Globalization, 1993-2005/ Renato Cruz de Castro 11. Globalization's Impact on Defence Industry in Southeast Asia/ Rommel C. Banlaoi 12. Globalization and the Defence Economy of South Asia:Two Views/ Vijay Sakhuja and Deba R. Mohanty 13. Conclusion/ Geoffrey Till.
1 Introduction Joshua Ho Part 1: Theories of Globalization and Defence 2 Globalization and Armed Conflict Among Nations: Prospects Through the Lens of International Relations Theory Brian Pollins 3 Beyond Interdependence: Globalization, State Transformation and National Security Christopher W Hughes Part 2: Globalization and Defence Policy in the Asia-Pacific 4 Globalization and Military-Industrial Transformation in South Asia: An Historical Perspective Emrys Chew 5 The Impact of Globalization on Threat Perceptions and Defence Postures in Northeast Asia Guibourg Delamotte 6 The Impact of Globalization on Threat Perceptions and Defence Postures in Southeast Asia: Two views Rizal Sukma and K S Nathan 7 The Impact of Globalization on Threat Perceptions and Defence Postures in South Asia B Rahman Part 3: Globalization and the Defence Economy in the Asia-Pacific 8 Defence and the Economy: An Introduction Ron Mathews 9 Globalization and Defence Industry in East Asia: Seeking Self-Sufficiency and Teaming Up for Dual-Use Technology Arthur S Ding 10 Exploring Southeast Asia's Twenty-First Century Defence Economies: Opportunites and Challenges in the Era of Globalization, 1993-2005 Renato Cruz de Castro 11 Globalization's Impact on Defence Industry in Southeast Asia Rommel Banlaoi 12 Globalization and the Defence Economy of South Asia:Two Views Vijay Sakhuja and Deba R Mohanty 13 Conclusion Geoffrey Till.
Includes index.
Keywords: Globalisering; Interdependens; Sikkerhedspolitik; Stillehavsomradet-Asien.; Sydasien